Dearomatization of Nitro(hetero)arenes through Annulation. Issue 18 (9th May 2022) - Wang, Ning; Ren, Jing; Li, Kaizhi
Abstract: Dearomatization reactions employing simple aromatic compounds have showcased remarkable progress in the recent decade and have emerged as one of the most straightforward and powerful tools for the creation of highly functionalized, three‐dimensional molecular frameworks commonly encountered in medicinal chemistry and life sciences. Among the aromatic compounds in use, nitro(hetero)arenes, which feature a less pronounced aromatic character due to the presence of highly electron‐withdrawing nitro group, have been extensively used in different types of dearomatization reactions. The dearomative annulation reaction serves as a powerful and versatile method for the construction of complex polycyclic systems. This overview presents a brief summary of recent impressive advances in nitro(hetero)arenes dearomative annulation and provides some inspirations for future research. Abstract : A summary of the recent literatures on dearomative annulation reactions involving nitro(hetero)arenes for the construction of synthetically important polycyclic systems has been described.